Pemetaan Instrumen Self-Efficacy Siswa Kelas V Pada Materi Ekosistem Di Sekolah Dasar - Nadia Adillah Harpizon; Risnawati Risnawati; Rian Vebrianto; M. Fikri Hamdani; Khairul Saleh (Journal on Education, 2024)
This study aims to determine: (1) the profile and ability of self-efficacy of grade V Pekanbaru students; and (2) differences in self-efficacy based on gender, age, ethnicity, ideals, parents' education and parents' occupation. This study used a quantitative approach through survey method, with a total sample of 50 people taken through cluster sampling technique. All data were collected through questionnaires that have been distributed and analyzed quantitatively using the IBM SPSS Statistics 25 application and the Two-Way Anova test. The results showed that: (1) in terms of self-efficacy, the research subjects have good self-efficacy on average (min = 6.7); (2) there is no difference in self-efficacy based on age, ethnicity, and parental education; and (3) there is a relationship between gender, ideals, and parental occupation. The teachers will further provide relevant inputs and actions to improve teachers' resources and skills.